Development of Hadith Learning Media in As-Salam Islamic Boarding School in Bengkulu City - Dhimas Alunandika; Saiful Amien (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
Many efforts are made in the field of education to update or innovate education. Educational management, methods, media, learning resources, curriculum, and many more are educational reforms. Based on this opinion, it can be understood that the activity, creativity, and motivation of students in learning can be improved through learning media. In addition, by utilizing learning media as support, the delivery of subject matter can be facilitated. This research will study the Development of Hadith Learning Media at Pondok Pesantren As-Salam Bengkulu City by using descriptive qualitative methodology. This method will allow researchers to explain, analyze, and describe in detail the Hadith Learning Media Development. The research subjects will consist of: A subject will be selected based on variations in his/her experience, media, and teaching methods. Data that will be analyzed qualitatively are collected to analyze the data. Learning media can not only increase the attention of students, but also can convey the message to be communicated. When teachers carry out learning in schools, they are able to create a learning atmosphere that collaborates with their students, utilizing the right learning media. active, innovative, effective, varied, and funThus, the learning process can be optimized in the most effective way and the main focus is to improve student achievement. The similarity lies in the material element, and the difference lies in the immaterial element. According to the hadith perspective, learning media is divided into audio, visual, and audio-visual categories. Learning media is useful as a tool or means to achieve learning objectives by conveying messages or information in the form of knowledge from various sources to the person receiving it.